A straightforward multiparametric quality control protocol for proton magnetic resonance spectroscopy: Validation and comparison of various 1.5 T and 3 T clinical scanner systems. (October 2018) - Sghedoni, Roberto; Coniglio, Angela; Mazzoni, Lorenzo Nicola; Busoni, Simone; Belli, Giacomo; Tarducci, Roberto; Nocetti, Luca; Fedeli, Luca; Esposito, Marco; Ciccarone, Antonio; Altabella, Luisa; Bellini, Alessandro; et al.
Highlight: Eighteen clinical scanners were enrolled in an MR-spectroscopy intercomparison study. The feasibility of a quality control protocol for routine MR-spectroscopy was proved. The water linewidth at isocenter was less than 0.03 ppm for 1.5 T and 3 T scanners. The area under the water peak varied linearly with the acquisition voxel volume. The coefficient of variation for repeated measurements of phantom T2 was less than 9%. Abstract: Purpose: The aim of this study was to propose and validate across various clinical scanner systems a straightforward multiparametric quality assurance procedure for proton magnetic resonance spectroscopy (MRS). Methods: Eighteen clinical 1.5 T and 3 T scanner systems for MRS, from 16 centres and 3 different manufacturers, were enrolled in the study. A standard spherical water phantom was employed by all centres. The acquisition protocol included 3 sets of single (isotropic) voxel (size 20 mm) PRESS acquisitions with unsuppressed water signal and acquisition voxel position at isocenter as well as off-center, repeated 4/5 times within approximately 2 months. Water peak linewidth (LW) and area under the water peak (AP) were estimated. Results: LW values [mean (standard deviation)] were 1.4 (1.0) Hz and 0.8 (0.3) Hz for 3 T and 1.5 T scanners, respectively. The mean (standard deviation) (across all scanners) coefficient of variation of LW and AP for different spatial positions of acquisition voxel were 43% (20%) and 11% (11%), respectively. The mean (standard deviation) phantom T2  values were 1145 (50) ms and 1010 (95) ms for 1.5 T and 3 T scanners, respectively. The mean (standard deviation) (across all scanners) coefficients of variation for repeated measurements of LW, AP and T2 were 25% (20%), 10% (14%) and 5% (2%), respectively. Conclusions: We proposed a straightforward multiparametric and not time consuming quality control protocol for MRS, which can be included in routine and periodic quality assurance procedures. The protocol has been validated and proven to be feasible in a multicentre comparison study of a fairly large number of clinical 1.5 T and 3 T scanner systems.